2004
DOI: 10.1128/aem.70.11.6897-6900.2004
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Nonylphenol Single Isomer by Sphingomonas sp. Strain TTNP3 Leads to a Hydroxylation-Induced Migration Product

Abstract: Sphingomonas sp. strain TTNP3 degrades 4(3,5-dimethyl-3-heptyl)-phenol and unidentified metabolites that were described previously. The chromatographic analyses of the synthesized reference compound and the metabolites led to their identification as 2(3,5-dimethyl-3-heptyl)-1,4-benzenediol. This finding indicates that the nonylphenol metabolism of this bacterium involves unconventional degradation pathways where an NIH shift mechanism occurs.Nonylphenol (NP) is a ubiquitous pollutant which mainly results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…In fact, this compound could be rationalized by an NIH shift mechanism, namely the migration of the substituent to the adjacent C atom consecutively with hydroxylation, followed by hydrogenation reactions. By analogy with studies with NP (8,14), a carbanionic shift of the isopropylphenol moiety to the adjacent carbon could occur. Another possibility is that the result of this NIH shift does not involve an intramolecular migration mechanism but rather a condensation reaction between the leaving carbocationic intermediate and the newly formed HQ (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this compound could be rationalized by an NIH shift mechanism, namely the migration of the substituent to the adjacent C atom consecutively with hydroxylation, followed by hydrogenation reactions. By analogy with studies with NP (8,14), a carbanionic shift of the isopropylphenol moiety to the adjacent carbon could occur. Another possibility is that the result of this NIH shift does not involve an intramolecular migration mechanism but rather a condensation reaction between the leaving carbocationic intermediate and the newly formed HQ (6).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations were carried out mainly with Sphingomonas sp. strain TTNP3 (6)(7)(8)(9)(10)(11) and S. xenophaga strain Bayram (13,14). In both strains, degradation pathways involve ipso-hydroxylation of NP as the first step (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive studies on the NP degradation pathways of Sphingomonas sp. TTNP3 and Sphingobium xenophagum Bayram revealed that NP can be oxidized at the aromatic carbon atom substituted with the alkyl side chain (ipso-hydroxylation) (Corvini et al, 2004(Corvini et al, , 2006aGabriel et al, 2005aGabriel et al, , b, 2007. From the oxidized intermediate, the aromatic moiety and the side chain are separated as hydroquinone and a carbocation with nine carbon atoms (finally forming an alcohol or several aliphatic compounds), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Certain microorganisms belonging to the bacterial and yeast groups have the ability to degrade NP (4,5,38,39). Recent studies have shown the abilities of selected fungi, including white rot fungi, to degrade this chemical, albeit to various extents (33).…”
mentioning
confidence: 99%